2016
DOI: 10.1021/acs.inorgchem.6b00804
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Zn(II) Complexes: Photophysical Properties and Catalytic Transesterification toward Biodiesel Synthesis

Abstract: Using 4-substituted derivatives of phenol-based compartmental Schiff-base hydroxyl-rich ligand, four multifunctional binuclear Zn(II) complexes have been synthesized and characterized. The photophysical properties of these complexes were explored in the solid state, in solutions, and in poly(methyl methacrylate) (PMMA) matrix, which revealed their good potential as tunable solid state emitters. Some of these complexes acted as efficient catalysts for the transesterification of esters and canola oil showing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…The process leading to Zn1–N1 bond cleavage can be understood thanks to the dimer metadynamics, the results of which are shown in Figure 5, in good agreement with the values reported for dimeric compounds with similar cores [46,63]. Despite the fact that many transient structures may exist for times smaller than femtoseconds, from now on we will focus exclusively on the main species (i.e., transition states and intermediates) and the chemical changes involved in the process under study.…”
Section: Resultssupporting
confidence: 85%
“…The process leading to Zn1–N1 bond cleavage can be understood thanks to the dimer metadynamics, the results of which are shown in Figure 5, in good agreement with the values reported for dimeric compounds with similar cores [46,63]. Despite the fact that many transient structures may exist for times smaller than femtoseconds, from now on we will focus exclusively on the main species (i.e., transition states and intermediates) and the chemical changes involved in the process under study.…”
Section: Resultssupporting
confidence: 85%
“…Tris buffer solutions are widely used in molecular and cellular biology for processes such as extraction and purification of proteins, DNA, RNA and nucleic acids, and are still used in clinical practice . On the other hand, there are examples of enzymatic catalytic activity of α‐chymotrypsin complexes used as fluorescent probes, compounds of rhodamine–spirolactam which act as double channels (on–off), anti‐inflammatory activity, photo‐bioreductive compounds, epoxide catalysts, photoluminescence and catalytic transesterification including biodiesel synthesis …”
Section: Introductionmentioning
confidence: 99%
“…In the same year, Gupta et al [89] . demonstrated that a binuclear photoluminescent complexes of zinc(II) is active in the transesterification of several substrates in mild conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In the same year, Gupta et al [89] demonstrated that a binuclear photoluminescent complexes of zinc(II) is active in the transesterification of several substrates in mild conditions. Nevertheless, the conversion of canola oil into biodiesel reached only 5 % yield in 24 h at 50°C with 0.01 % mol of catalyst and a molar ratio of about 2000 : 1.…”
Section: Transesterification Of Triglycerides For Biodiesel Synthesismentioning
confidence: 99%